2014
DOI: 10.1159/000360266
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Body Laterality on Recovery from Subjective Visual Vertical Tilt after Vestibular Neuritis

Abstract: The subjective visual vertical (SVV) is an indicator of vestibular otolithic function and mainly processed by the nondominant parietal cortex. We investigated the hypothesis that recovery from SVV tilt after vestibular neuritis can be influenced by the body's lateral preference. This prospective cohort follow-up study included 254 consecutive adult patients with vestibular neuritis. The recovery from SVV tilt was faster in patients with a left hand or eye dominance than in those with a right dominance. While i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…The difference of coping strategy between a left and a right disease is in line with the results of a previous study on the regression of SVV tilt after vestibular neuritis. In this previous study, we showed that the side of the neuritis influenced the speed of SVV tilt recovery and that patients with a left deficit recovered faster than those with a right weakness (20).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The difference of coping strategy between a left and a right disease is in line with the results of a previous study on the regression of SVV tilt after vestibular neuritis. In this previous study, we showed that the side of the neuritis influenced the speed of SVV tilt recovery and that patients with a left deficit recovered faster than those with a right weakness (20).…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, these studies indicate the potential role of sex hormone impregnation (i.e., progesterone and estrogen) in these capacities and the modulation of these cerebral performances by the hormone levels during the menstrual cycle (16,19). The exact pathophysiological mechanisms of sex hormone influence on visuomotor tasks are still unclear (20).…”
Section: Discussionmentioning
confidence: 98%
“…While this bias slowly decreases, not all patients reach normal values after months to years (Friedmann, 1970, Curthoys et al , 1991, Böhmer et al , 1995, Tribukait et al , 1998, Hafström et al , 2004, Hafstrom et al , 2006, Lopez et al , 2008, Toupet et al , 2014, with adjustment errors between -2.0° and 11.7°. These results are consistent with our observation of a trend (3.7±2.0°, p=0.100) towards an ipsilesional SVV bias when upright.…”
Section: Discussionmentioning
confidence: 99%
“…Objective clinical tests of vestibular end‐organ function have been well established for the lateral semicircular canal (rotary chair and caloric tests) and the saccule (cervical vestibular evoked myogenic potential test), but options for testing the function of the other vestibular end organs are limited. The subjective visual vertical (SVV) test has been shown to be a useful test for unilateral peripheral vestibular impairment involving the utricle . Acute injuries to central vestibular pathways can also affect SVV .…”
Section: Introductionmentioning
confidence: 99%